Measuring Serum Level of Ionized Magnesium in Patients with Migraine - ASSARZADEGAN, Farhad; ASADOLLAHI, Mostafa; DERAKHSHANFAR, Hojjat; KASHEFIZADEH, Azam; ARYANI, Omid; KHORSHIDI, Mona (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Assarzadegan F, Asadollahi M, Derakhshanfar H, Kashefizadeh A, Aryani O, Khorshidi M. Measuring Serum Level of Ionized Magnesium in Patients with Migraine. Iran J Child Neurol. Summer 2015;9(3):13-16. Abstract Objective Migraine is known as one of the most disabling types of headache. Among the variety of theories to explain mechanism of migraine, role of serum magnesium is of great importance. Serum magnesium, as a pathogenesis factor, was considerably lower in patients with migraine. We established this study to see if serum ionized magnesium, not its total serum level, was different in migraineurs from normal individuals. Materials & Methods In this case control study, all participants were recruited from Neurology Clinic of Imam Hossein Hospital, Tehran, Iran. Ninety-six people were entered in the study, 48 for each of case and control groups. The two groups were matched by age and sex. Migrainous patients were selected according to the criteria of International Headache Society. Various characteristics of headache were recorded based on patients’ report. Controls had no history of migraine or any significant chronic headaches. Serum ionized magnesium level was measured in both of the case and control groups and the results were compared to each other. P value of <0.05 was considered as significant. Results Case group consisted of 13 males, 35 females, and control group included 14 males, as well as 34 females. Mean age was 33.47± 10.32 yr for case and 30.45 ±7.12 yr for control group. Twenty-eight patients described the intensity of their headaches as moderate; 15 patients had severe and the 5 remainders had only mild headaches. Mean serum level of ionized Mg was 1.16± 0.08 in case group and 1.13± 0.11 in control group of no significant difference (P >0.05). Conclusion Serum ionized magnesium, which is the active form of this ion, was not significantly different in migraineurs and those without migraine. This may propose a revision regarding pathogenesis of migraine and question the role of magnesium in this type of headache.